2015
DOI: 10.1155/2015/475159
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Algorithm of Constructing Virtual Backbone Scheduling for Maximizing the Lifetime of Dual-Radio Wireless Sensor Networks

Abstract: Wireless sensor networks have often been used to monitor environmental conditions, such as temperature, sound, and pressure. Because the sensors are expected to work on batteries for a long time without charging their batteries, the major challenge in the design of wireless sensor networks is to enhance the network lifetime. Recently, many researchers have studied the problem of constructing virtual backbones, which are backbones used for different time periods, to prolong the network lifetime. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In addition, the authors showed that the MLDATS problem is NP-complete. In [28], the author proposed a distributed algorithm to find a backbone in the dual-radio network whenever a new backbone was needed; and examined the difficulty of constructing virtual backbones to increase the network lifetime.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, the authors showed that the MLDATS problem is NP-complete. In [28], the author proposed a distributed algorithm to find a backbone in the dual-radio network whenever a new backbone was needed; and examined the difficulty of constructing virtual backbones to increase the network lifetime.…”
Section: Related Workmentioning
confidence: 99%
“…Authors in [67] investigated the problem of constructing virtual backbones to increase the network life and proposed a distributed algorithm to find a backbone in the dual-radio network whenever a new backbone is needed. Similarly, a virtual backbone construction heuristic for maximizing the network lifetime in dual-radio based WSNs was proposed in [68].…”
Section: Related Workmentioning
confidence: 99%
“…We investigate the energy efficiency problem in WSNs from an entirely different perspective wherein the security against the previously mentioned attacks, the filtering strength of the available intermediate routes (for example: the number of verification keys on the path and the average distance of verification nodes from the data generating cluster) are considered while developing a heuristic based solution for path selection that provides the maximum security against the FVIA and FRIA attacks at the same time. In contrast, the solutions proposed in [67,68] are scheduling strategies that consider the energy power of the nodes while constructing a backbone. One of the important pieces of information required in choosing the energy efficient path for data dissemination is the number of upstream nodes holding the corresponding data authentication keys and their distances from the data generating cluster.…”
Section: Related Workmentioning
confidence: 99%
“…and reach optimum performance with a safe, therapeutic technique for sports injury rehabilitation. One can get an exercise prescription suited to specific needs (Liu et al, 2015). Sports injury rehabilitation is essential for ensuring that return to activities is feasible and safe.…”
mentioning
confidence: 99%